Application of Nitrate–Ammonium Nitrogen Fertilization Reduced Nitrogen Loss in Surface Runoff and Infiltration by Improving Root Morphology of Flue-Cured Tobacco - Chengren Ouyang; Kang Yang; Zhengxiong Zhao (Agronomy)
Nitrogen loss in water from farmland has become an environmental issue. Nitrogen fertilizer is the main cause of agricultural non-point source pollution in the Lake Basin, Yunnan. However, it is unclear how different nitrogen fertilizer forms affect water loss from farmland and how the root systems of crops respond. We established five nitrogen fertilizer treatments (100–0% [T1], 75–25% [T2], 50–50% [T3], 25–75% [T4], and 0–100% [(T5)] nitrate–ammonium) and performed an investigation to determine nitrogen loss in water and root morphological parameters of tobacco in Mile County and Chengjiang County. Compared with in the T1, T4, and T5 treatments, the total nitrogen loss in surface runoff was reduced by 4.67%, 11.85% and 9.56% in the T2 treatment and 27.32%, 23.20%, and 31.43% in the T3 treatment, respectively. Similar results were observed for the nitrogen loss due to infiltration. The root biomass was negatively correlated with nitrogen loss. There was greater root biomass, root surface area, and root spatial distribution in T2 and T3 compared with in T1, T4, and T5. These results indicate that 50–50% nitrate–ammonium nitrogen fertilizer can facilitate the root growth of tobacco and reduce nitrogen loss, which provides a reference for agricultural sustainable development.